2015
DOI: 10.1017/ice.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changes in the NHSN Catheter-Associated Urinary Tract Infection (CAUTI) Surveillance criteria on the Frequency and Epidemiology of CAUTI in Intensive Care Units (ICUs)

Abstract: The impact of the 2013 NHSN CAUTI definition on CAUTI rates was analyzed. A total of 107 CAUTI episodes were identified; 60 according to NHSN 2013 definitions only and 47 according to the 2012 and 2013 definitions. Physician-diagnosed "other infections" were more common among patients who had CAUTI only according to NHSN 2013 definitions (P<.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…In consistence, most of CAUTI patients fever has many causes of admission including pneumonia, bloodstream infection, or an intracranial bleed (13) . This is also in the same pattern with other previous studies (14,15) .…”
Section: Discussion:-supporting
confidence: 92%
“…In consistence, most of CAUTI patients fever has many causes of admission including pneumonia, bloodstream infection, or an intracranial bleed (13) . This is also in the same pattern with other previous studies (14,15) .…”
Section: Discussion:-supporting
confidence: 92%
“…Prior studies have reported that patients in the ICU with CAUTI often have alternative diagnoses to explain the fever. 7,8 In a study of 105 CAUTIs in ICU patients, 51% had another infection (primarily pneumonia), and 18% had noninfectious conditions as alternative explanations for fever. 7 The lower rate of 9% of CAUTIs with concurrent infection as a possible cause of fever in our study is likely because of the more stringent criteria used, namely infections confirmed by positive cultures from a sterile site.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore epidemiological surveillance and outbreak investigations, together with infection control polices and interventions, such as the use of protective barriers and proper disinfection, are key for infection control of these organisms in the nosocomial environment ( Sydnor and Perl, 2011 ). High-level enterococcal GIT colonization can also lead to urinary tract infections (UTI) ( De Vecchi et al, 2013 ; Neelakanta et al, 2015 ), which may progress to bloodstream infections or endocarditis ( Patterson et al, 1995 ; Fern谩ndez-Guerrero et al, 2002 ). Enterococci from high-density intestinal populations may also directly translocate from the GIT into the bloodstream ( Kamboj et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%